The opposable mind winning through integrative thinking - Martin, Roger (Boston Harvard Business Press, 2009)
"According to the bestselling author Roger Martin, such brilliant leaders are skilled at integrative thinking: the ability to hold two opposing ideas in their mind at once, and then reach a synthesis that contains elements of both but actually improves on each. By refusing to accept unpleasant trade-offs and conventional options, integrative thinkers are able to find creative solutions to seemingly intractable problems. But is integrative thinking a talent reserved for a fortunate few? Martin says no. He believes it's a habit of thought that anyone can consciously develop to arrive at fresh and creative solutions. This book is your guide to getting here." -- Provided by publisher
Keywords: Leadership -- Psychological aspects; Thought and thinking; Problem solving